The Windscreen World of Land Use Transport Integration: Experiences from Perth, a Dispersed City - Curtis, Carey (2005)
'Land use transport integration' has been part of planning ideology for decades. Today it is seen as a means of achieving sustainable travel outcomes. Despite the clear intentions of early planning policy, its selective implementation resulted in a low-density, dispersed city. Now the ability to reduce motorised travel and car kilometres is a major challenge given the spread of land use and scatter of activity across a very large metropolitan area. The 'love affair with the car' has seen a struggle for focus on access for pedestrians, cyclists and public transport. But the more recent experience in the context of this dispersed city is promising, urban development is achieving some of the physical characteristics of land use transport integration with greatest progress made in recent years. At the neighbourhood scale there are small 'islands' of development change with a strong focus on achieving accessibility, proximity and creation of shared streets. At the metro/regional scale the focus is on extending the rail network, but city planning is still driven by 'car-centric' principles the windscreen view of the world. Designing a transport system to compete with the car, rather than tailoring the demand for mobility by designing a different spatial land use pattern perpetuates hypermobility and automobility.